Experience in genetic testing of hypertrophic cardiomyopathy using nanopore DNA sequencing - R. R. Salakhov; M. V. Golubenko; E. N. Pavlukova; A. N. Kucher; N. P. Babushkina; N. R. Valiahmetov; A. V. Markov; E. O. Belyaeva; A. F. Kanev; M. S. Nazarenko (Российский кардиологический журнал)
Aim. To investigate the application of the Oxford Nanopore Technologies’ third generation sequencing for the genetic testing of hypertrophic cardiomyopathy.Material and methods. The study involved 12 patients with hypertrophic cardiomyopathy aged 18 to 67 years (women, 9; men, 3). Using the PCR barcoding amplicons (SQK-LSK109) protocol, DNA libraries were created which contained long-range PCR fragments of the MYH7, MYBPC3, TNNT2, TNNI3 and TPM1 genes. The sequencing was performed using the MinION system by Oxford Nanopore Technologies (UK). Bioinformatic algorithms for data analysis included Guppy v.5.0.7, Nanopolish and Clairvoyante. The identified genetic variants were confirmed by Sanger sequencing.Results. Data on the complete sequence of the five major sarcomeric genes for hypertrophic cardiomyopathy were obtained. We found eight potentially disease-causing sequence variants in MYH7, MYBPC3 and TNNT2 genes by monomolecular sequencing. However, only three mutations p.Arg243Cys, p.Tyr609Asn, p.Arg870His in the MYH7 gene, and one mutation p.Lys985Asn in the MYBPC3 were confirmed by Sanger sequencing. Cascade screening of pathogenic variant p.Arg870His in the MYH7 gene was performed. We found one asymptomatic carrier.Conclusion. It appears that monomolecular sequencing technology is a feasible approach to identify mutations in patients with hypertrophic cardiomyopathy. Although improvement in accuracy of DNA sequencing, as well as optimization and simplification of bioinformatic algorithms for identification of the genetic variants are needed.